Evaluasi dan Perbaikan Proses Bisnis Pembacaan Meter Pascabayar di PT PLN (Persero) UP3 Malang - Muhammad Indra Firdaus; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
PT PLN (Persero) UP3 Malang is one of the PLN business units which has the obligation to serve prospective customers and the public related to the sale of electricity. Postpaid meter reading is one of the important business processes at PT PLN (Persero) UP3 Malang. There are several problems that occur in the postpaid meter reading business process, including errors when inputting data, customers included in incorrect meter reading route, errors in meter reading, and difficulties in taking meter readings because the house is closed or the fence is locked which results in losses for PLN because they do not get accurate calculation results. Therefore, it is necessary to evaluate the postpaid meter reading business process to assess whether the postpaid meter reading business process is appropriate with performance indicators in the postpaid meter reading business. To evaluate the business process, the root cause of the problem in the postpaid meter reading business process was identified using the 3 x 5 Whys technique. After that, for problematic activities, recommendations are given using the 12 streamlining tools contained in the Business Process Improvement (BPI) method. The recommended business process is then simulated and compared with the current business process to see the average time. The simulation results show that there is a decrease in the average time of 4 hours 8 minutes 18 seconds or 3.26% so it can be said that improvements in postpaid meter reading business process can solve the problems contained in the business process.